2011
DOI: 10.1080/09603123.2010.515672
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of the bacterial flora of vegetables collected directly from farms and from supermarkets in Germany

Abstract: A total of 1,001 vegetables were collected from 13 farms and 11 supermarkets in Bavaria, Germany; 722 samples were positive for coliforms (mostly Enterobacter cloacae; n = 176). Escherichia coli were detected in 34, Pseudomonas spp. in 439, Salmonella spp. in 1, Enterococcus spp. in 682, and Listeria spp. in 11 samples. Prevalence of all investigated genera tended to be lower in samples collected at the supermarket. However, prevalence of Pseudomonas fluorescens was higher in supermarket samples. Cereals/bulbo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 51 publications
(48 reference statements)
2
11
1
Order By: Relevance
“…Presumably, the washing processes should have produced a lower prevalence rate. However, our results contrasted with those of Schwaiger et al [42], who showed a higher resistance rate of bacteria from farms than from the retail markets. Comparisons might not be relevant in our case given the recorded deficits in risk reduction practices on farms and improper post-harvest washing practices.…”
Section: Multiple Drug Resistancecontrasting
confidence: 57%
“…Presumably, the washing processes should have produced a lower prevalence rate. However, our results contrasted with those of Schwaiger et al [42], who showed a higher resistance rate of bacteria from farms than from the retail markets. Comparisons might not be relevant in our case given the recorded deficits in risk reduction practices on farms and improper post-harvest washing practices.…”
Section: Multiple Drug Resistancecontrasting
confidence: 57%
“…An isolation percentage of 4.18% (8/191) was obtained, what agrees with other studies conducted in Spain, where L. monocytogenes was isolated in 8 out of 103 samples (7.80%) of raw vegetables (Simon, Tarrago & Ferrer, 1992). In a recent german study (Schwaiger, Helmke, Holzel & Bauer, 2011), in 1001 investigated vegetables, only four L. monocytogenes were found. In Italy, L. monocytogenes was isolated from a total of 7/102 (6.90%) samples of different raw vegetables (Gola, Previdi, Mutti & Belloi, 1990) and in Ireland in 3/21 (14.30%) of packed under MAP fresh-cut salads ready for consumption with ingredients such as cabbage, carrots and lettuce (Harvey & Gilmour, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…The highest concentration of Cr was found in CSH Pharmaceutical (Pvt), while the lowest one was found in Attock Chemical Industry (p < 0.05). The reported amount of this metal in human body is approximately 0.03 ppm [32]. The daily intake of Cr in normal human from different sources is approximately 15-200 μg, which may sometimes reach up to 1 mg [33].…”
Section: Heavy Metals Concentrationmentioning
confidence: 99%